Capability of the Mediterranean Argo network to monitor sub-regional climate change indicators - Chevillard, Carla; Juza, Mélanie; Díaz-Barroso, Lara; Reyes, Emma; Escudier, Romain; Tintoré, Joaquín (Frontiers in Marine Science, 2024)
The Argo array of profiling floats has considerably increased the observing capability of the three-dimensional global ocean and the knowledge of the ocean response to climate change. In particular, the Argo sampling has allowed observing relevant ocean indicators over the whole Mediterranean Sea especially during the last decade. In this study, the Mediterranean Argo network is comprehensively described from its spatio-temporal coverage to its capability to observe ocean monitoring indicators at sub-regional scale. For this purpose, the Argo array, as a non-interpolated product of profiles, is used to estimate the ocean heat and salt contents integrated within the upper, intermediate and deep layers over the period 2013-2022 in the different sub-regions of the basin. The same computational method is also applied to a model reanalysis product to estimate the impact of sampling of the sole Argo array. The sampling error is defined at sub-regional scale by comparing estimations from the whole model grid (full-sampled model) and from the Argo-like sampled model grid (sub-sampled model). Warming and salinification trends are well captured by the Argo array over the period of study, warming trends being the highest in the sub-regions of the western Mediterranean Sea from surface to depth and salinification trends being higher in the eastern sub-basin for the upper layer and in the western sub-basin for the deeper layers. This study also demonstrates the capability of the Argo array to capture local ocean structures and dynamics (e.g. anticyclonic and cyclonic gyres, intermediate and deep convection events and Atlantic Water inflows) and to account for their impact in the sub-regional variability of ocean heat and salt contents in the upper, intermediate and deep layers from seasonal to interannual scales. Considering these structures is fundamental for the understanding of the thermohaline circulation and changes observed in the Mediterranean Sea, and thus for future climate studies.